PENGGUNAAN APLIKASI PADLET DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS VIII DI SMPN 6 MADIUN - Tahnia; Sumiyati; Neny; Marsiti; Sudarmiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aimed to improve the critical thinking skills and social studies (IPS) learning outcomes of eighth-grade students at SMP Negeri 6 Madiun through the use of Padlet, a collaborative digital learning application. The background of this study was the low level of students' critical thinking skills and learning outcomes, shown by pre-cycle data with an average critical thinking score of 50.00% and an average learning outcome of 67.57, with classical mastery of only 33%. This study followed the Kemmis and McTaggart action research model, carried out in two cycles, each consisting of planning, action, observation, and reflection stages, involving 31 eighth-grade students. Critical thinking data were collected through observation sheets based on four indicators, while learning outcome data were collected through written tests at the end of each cycle. The results showed that Padlet improved students' critical thinking skills from 50.00% in the pre-cycle to 68.13% in cycle I and 81.25% in cycle II. The average learning outcome score increased from 67.57 to 74.27 in cycle I and 82.90 in cycle II, with classical mastery rising from 33% to 57% in cycle I and 97% in cycle II. It is concluded that the use of Padlet in IPS learning is effective in improving